HTLV-1's Foxy Strategy for Survival and Transmission - Higuchi, Yusuke; Yasunaga, Jun-ichirou; Matsuoka, Masao (Frontiers in Virology, 2022)
Human T-cell leukemia virus type 1 (HTLV-1) is the causative agent of adult T-cell leukemia-lymphoma (ATL) and inflammatory diseases including HTLV-1-associated myelopathy (HAM). A remarkable feature of HTLV-1 is that this virus transmits primarily through cell-to-cell contact. HTLV-1 increases the number of infected cells in vivo to ensure its survival and transmission. Therefore, survival of HTLV-1-infected cells in vivo is very critical for transmission under the host immune surveillance. HTLV-1 possesses multiple strategies to evade host immune responses. Among viral genes, Tax and HTLV-1 bZIP factor (HBZ) play crucial roles in the proliferation of infected cells and the subsequent development of ATL. Although Tax strongly activates the NF-kB pathway, the immunogenicity of Tax is very high; it is a major target of cytotoxic T lymphocytes. Therefore, the virus minimizes Tax production, expressing it only intermittently in vivo. On the other hand, the immunogenicity of HBZ is low, and its expression is maintained in all ATL cases. HBZ transforms the immunophenotype of infected cells into regulatory T cell-like (CD4+ CD25+ CCR4+ TIGIT+ Foxp3+), and promotes the production of immunosuppressive cytokines. Furthermore, HBZ mRNA not only encodes the protein but also functions itself like long non-coding RNA. As a result, Tax and HBZ enable long-term escape from host immunity, persistent infection, and proliferation of infected cells. Here, we review the viral strategies to counteract to host immune surveillance system.